1976
DOI: 10.1002/path.1711180205
|View full text |Cite
|
Sign up to set email alerts
|

The fine structure of neoplastic invasion: Invasion of liver, skeletal muscle and lymphatic vessels by the Rd/3 tumour

Abstract: Neoplastic invasion as seen in the rat Rd/3 neoplasm has been studied electron microscopically in three sites: abdominal wall, footpad and liver. This neoplasm invades by peripheral cell division and active cell migration. Neoplastic cells protrude many fine processes and compress host cells. Neoplastic cells invade lymphatic vessels in a way similar to that in which white blood cells penetrate them - by the protrusion of fine cytoplasmic processes and passage, sometimes in clumps through open cell junctions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
1
1

Year Published

1976
1976
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(20 citation statements)
references
References 14 publications
1
17
1
1
Order By: Relevance
“…DISCUSSION Tumor cell attachment to and invasion of endothelial monolayers in tissue culture appeared to be similar to blood-borne tumor arrest and extravasation in vivo. Various studies (4,5,35,36) on tumor cell extravasation have suggested that neoplastic cells invade blood vessels at sites near or at endothelial intercellular junctions that are broken and subsequently reseal after tumor cell penetration, in a manner analogous to leukocyte emigration (37). However, in contrast to some reports (38)(39)(40), tumor cells in our studies were never observed to penetrate directly through endothelial cytoplasms.…”
contrasting
confidence: 55%
See 1 more Smart Citation
“…DISCUSSION Tumor cell attachment to and invasion of endothelial monolayers in tissue culture appeared to be similar to blood-borne tumor arrest and extravasation in vivo. Various studies (4,5,35,36) on tumor cell extravasation have suggested that neoplastic cells invade blood vessels at sites near or at endothelial intercellular junctions that are broken and subsequently reseal after tumor cell penetration, in a manner analogous to leukocyte emigration (37). However, in contrast to some reports (38)(39)(40), tumor cells in our studies were never observed to penetrate directly through endothelial cytoplasms.…”
contrasting
confidence: 55%
“…Two critical stages during blood-borne metastatic spread are circulating tumor cell (a) arrest or attachment to the vascular endothelium and (b) extravasation or invasion of the vascular endothelium and underlying basement membrane. Although little is known concerning the mechanism of blood-borne tumor cell arrest (2,3), several theories have been proposed for extravasation: (i) endothelium penetration by breakage of endothelial intercellular junctions (4,5), (ii) cytotoxic or enzymatic destruction of endothelial cells adjacent to tumor cells (6,7), (iii) extension of tumor cell pseudopodia through endothelial cell cytoplasm (8), and (iv) endothelial vessel rupture due to proliferation of tumor cells at the site of arrest (4). Due to the difficulties in studying tumor cell extravasation in vivo we have developed an in vitro model to evaluate malignant tumor cell interactions with vascular endothelial cells.…”
mentioning
confidence: 99%
“…This cessation was not an artefact of our perfused-liver model, since it also occurred in vivo. The extension of protrusions has often been seen as an initial step in infiltration by both tumour cells (Fisher and Fisher, 1961;Babai and Tremblay, 1972;Dingemans, 1973;Fasske et al, 1975;Carr et al, 1976;Chew et al, 1976;Roos et al, 1977) and leucocytes (Dingemans, 1978). The ballooning of these protrusions, which then become globular invasive processes, is apparently also important.…”
Section: Discussionmentioning
confidence: 99%
“…2) Interacción transcelular, reportada por Babaï (1976), y 3) Invasión intrasarcoplásmica, es la interacción más rara y con peor pronóstico en pacientes que la presentaron, se caracteriza por la invasión de las células cancerosas al interior de las fibras del músculo esquelético, con la aparición de agregados de células tumorales en el sarcoplasma (Carr et al, 1976;Slatkin & Pearson, 1976;Stratton et al, 1982).…”
Section: Introductionunclassified